Pembentukan Konseling Kelompok Menggunakan Pendekatan Logoterapi pada Lansia dengan Sindrom Sarang Kosong - Renidayati Renidayati; Nevi Yarni S; Netrawati Netrawati; Rezki Hariko (Jurnal Sehat Mandiri, 2025)
Older adulthood is a life phase marked by complex psychosocial changes, one of which is Empty Nest Syndrome, characterized by feelings of loneliness, loss of roles, and diminished meaning in life after adult children leave home. This study aims to examine the formation of group guidance and counseling using a logotherapy approach as a psychological intervention for older adults experiencing Empty Nest Syndrome. A descriptive qualitative approach was employed, focusing on the development and implementation of logotherapy-based group counseling. Data were collected through observation, semi-structured interviews, documentation, and pre- and post-intervention assessments using the Meaning in Life Questionnaire, Geriatric Depression Scale, and Loneliness Scale. The results indicate that group logotherapy counseling effectively enhances meaning in life, psychological well-being, and reduces feelings of loneliness among older adults. The effectiveness of the intervention is influenced by participant readiness, facilitator competence, optimal group size (6–10 participants), and the selection of appropriate settings and session schedules suited to older adults’ conditions. In conclusion, logotherapy-based group counseling can be used as an effective psychosocial intervention strategy to improve the quality of life of older adults experiencing Empty Nest Syndrome.